Development of gas transportation companies’ economic security level evaluation method by taxonometric method - Prokopiv, Mykhailo (Technology audit and production reserves, 2017)
The object of research is the process of assessing the state of ensuring economic security of gas transport enterprises. One of the biggest problems faced by scientists in determining the level of economic security is the problem of the extent to which the indicator affects the overall state of the enterprise. In the course of the study, a method of variation is used to solve this problem, which allows to avoid subjective judgments by the method of «expert assessments», and also allows to adjust the values of indicators taking into account their weight. The key difference between the methods is that in the calculation, the so-called standardization is done-bringing the absolute and relative values of the indicators to a dimensionless value. This allows to increase the range of indicators to determine the level of economic security. As a result, an integral indicator of the level of economic security of a gas transportation enterprise is obtained, not only solves the weaknesses of other methods, but also takes into account the peculiarities of the gas transportation industry. Due to this, it is possible to obtain as accurate as possible data on the state of economic security, as well as on the indices of significance of the components of the activities of the gas transportation enterprise. In comparison with similar methods, the proposed method allows to develop an effective model of enterprise management, which ensures stable development and avoids adverse factors or threats. The efficiency of the model lies in the overall activity of the enterprise, taking into account the shortcomings of other methods and features of the gas transportation industry.